2023
DOI: 10.1097/bsd.0000000000001441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative 12-item Short Form Mental Composite Scores on Clinical Outcomes in Cervical Disc Replacement

Abstract: Study Design: Retrospective cohort study. Objective: We aim to examine the effects of preoperative mental health status on demographic, perioperative characteristics, and postoperative outcomes in patients undergoing cervical disc replacement (CDR). Summary of Background Data: The effect of preoperative mental health status has not been widely studied in CDR. Methods: Patients undergoing primary CDR were retrospectively collected and stratified into 2 cohorts by 12-item Short Form Survey Mental Composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
1
1
1
Order By: Relevance
“…Further, rates of clinically meaningful improvement in physical function, pain, and disability outcomes were similar between cohorts. As such, the findings in this present study typically correspond with the previously mentioned studies, where worse baseline mental health prognosticates inferior postoperative clinical outcomes 3–7,15 . Of note, our study demonstrated a superior magnitude of improvement and MCID achievement for mental health outcomes in patients with worse baseline mental health, which was not reported in some of these previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Further, rates of clinically meaningful improvement in physical function, pain, and disability outcomes were similar between cohorts. As such, the findings in this present study typically correspond with the previously mentioned studies, where worse baseline mental health prognosticates inferior postoperative clinical outcomes 3–7,15 . Of note, our study demonstrated a superior magnitude of improvement and MCID achievement for mental health outcomes in patients with worse baseline mental health, which was not reported in some of these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…As such, the findings in this present study typically correspond with the previously mentioned studies, where worse baseline mental health prognosticates inferior postoperative clinical outcomes. [3][4][5][6][7]15 Of note, our study demonstrated a superior magnitude of improvement and MCID achievement for mental health outcomes in patients with worse baseline mental health, which was not reported in some of these previous studies. However, the magnitude of postoperative improvement and MCID achievement were similar between cohorts for physical function, pain, and disability outcomes.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation